2020
DOI: 10.1093/mnras/staa025
|View full text |Cite
|
Sign up to set email alerts
|

Evolving pulsation of the slowly rotating magnetic β Cep star ξ1 CMa

Abstract: Recent BRITE-Constellation space photometry of the slowly rotating, magnetic β Cep pulsator ξ 1 CMa permits a new analysis of its pulsation properties. Analysis of the twocolour BRITE data reveals the well-known single pulsation period of 0.209 d, along with its first and second harmonics. A similar analysis of SMEI and TESS observations yields compatible results, with the higher precision TESS observations also revealing several low-amplitude modes with frequencies below 5 d −1 ; some of these are likely g mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
(100 reference statements)
0
5
0
Order By: Relevance
“…HD 46328 (ξ 1 CMa, B0.5 IV, Lesh 1968) is a well-studied high-amplitude β Cep star, with a single pulsation period of P = 0.209 d (McNamara 1955;Shobbrook 1973b;Heynderickx 1992;Heynderickx et al 1994;Saesen et al 2006;Shultz et al 2017Shultz et al , 2018Wade et al 2020b). Its one-sector TESS data set was most recently studied by Wade et al (2020b), who recover this period again and use it to constrain the period change over the last 100 yr. They also note the possible presence of g modes.…”
Section: Appendix B: Comments On Individual Objectsmentioning
confidence: 99%
“…HD 46328 (ξ 1 CMa, B0.5 IV, Lesh 1968) is a well-studied high-amplitude β Cep star, with a single pulsation period of P = 0.209 d (McNamara 1955;Shobbrook 1973b;Heynderickx 1992;Heynderickx et al 1994;Saesen et al 2006;Shultz et al 2017Shultz et al , 2018Wade et al 2020b). Its one-sector TESS data set was most recently studied by Wade et al (2020b), who recover this period again and use it to constrain the period change over the last 100 yr. They also note the possible presence of g modes.…”
Section: Appendix B: Comments On Individual Objectsmentioning
confidence: 99%
“…Building on work by Pigulski [71], Jerzykiewicz [72] and Shultz et al [69], BRITE-Constellation photometry (BLb, BHr, BTr) of ξ 1 CMa was employed by Wade et al [73], as one of the most recent anchor points to monitor the evolution of its pulsation period. Combining over one century of photometric and radial velocity monitoring, they concluded that the period evolution of ξ 1 CMa consists of a secular period lengthening of roughly 0.3 s/century that can be satisfactorily understood as a consequence of expansion due to stellar evolution.…”
Section: Evolving Pulsation Of the Slowly Rotating Magnetic β Cephei Pulsator ξmentioning
confidence: 99%
“…We calculated RV measurements (Table A1) from the individual subexposures of the spectropolarimetric sequences, following the multiline procedure described by . The RVs from the 2019 observations were published by Wade et al (2020). To calculate pulsation phase, we adopt the nonlinear ephemeris (P 0 = 0.2095763(1) d and Ṗ = 0.0096(5) s yr −1 ) from , consistent with the short-term period evolution described by Wade et al (2020).…”
Section: Espadons Spectropolarimetrymentioning
confidence: 99%
“…The RVs from the 2019 observations were published by Wade et al (2020). To calculate pulsation phase, we adopt the nonlinear ephemeris (P 0 = 0.2095763(1) d and Ṗ = 0.0096(5) s yr −1 ) from , consistent with the short-term period evolution described by Wade et al (2020).…”
Section: Espadons Spectropolarimetrymentioning
confidence: 99%
See 1 more Smart Citation